CONVERTIBLE SECURITIES AND HETEROGENEITY OF INVESTOR BELIEFS. (June 2015) - Jiao, Jie; Yan, An
Abstract We conjecture that convertibles can better attract investors with different beliefs about a firm's future cash flows compared to straight bonds and stocks. Our empirical findings are consistent with this conjecture. We find that a firm is more likely to issue convertibles rather than seasoned stocks and straight bonds in the public markets when investors' beliefs are more heterogeneous. The positive effect of heterogeneous beliefs on the relative likelihood of convertibles is greater when investors are more optimistic. Overall, our findings provide a novel rationale based on investors' heterogeneous beliefs for the use of convertibles in corporate external financing decisions.